Effects of extracellular pH, PCO2 and HCO3- on intracellular pH in isolated type-I cells of the neonatal rat carotid body. - Buckler, K; Vaughan-Jones, R; Peers, C; Lagadic-Gossmann, D; Nye, P (1991)
1. The effects of changing PCO2 extracellular pH (pHo) and HCO3- on intracellular pH (pHi) were studied in isolated neonatal rat type-I carotid body cells using the pH-sensitive fluoroprobe, carboxy-SNARF-1. 2. Simulated respiratory acidosis and alkalosis (i.e. changes in PCO2 at constant HCO3-) led to rapid (half-time t0.5 = 3 s) monotonic changes in pHi. The relationship between pHi and pHo under these conditions was linear, steep (0.63 pHi/pHo) and remarkably similar to the response predicted from a passive cell model (i.e. a cell lacking pHi regulation). 3. In order to model the above pHi changes (point 2), it was necessary to determine beta i (intrinsic intracellular buffering power). By using small incremental acid loads in the cell (progressive [NH4+]o removal), beta i was determined as a function of pHi to be: beta i = 127.6-16.04 pHi. 4. Changes in PCO2 at constant pHo (i.e. simultaneously changing HCO3-) caused rapid transient changes in pHi but did not significantly affect steady-state pHi over the range 1-10% CO2. 5. When PCO2 was held constant (5%), changing HCO3- and thus pHo (i.e. a simulated metabolic acidosis/alkalosis) led to much slower changes in pHi (t0.5 approximately 1 min). Steady-state pHi showed an almost identical dependence on pHo (slope 0.68) to that found for simulated respiratory acidosis/alkalosis. Therefore, over the range of pHo, PCO2 and [HCO3-]o tested, steady-state pHi appeared to be a unique function of pHo and independent of PCO2 and [HCO3-]o. 6. The effects on pHi of respiratory acidosis, metabolic acidosis and increases of PCO2 at constant pHo (present work) were compared with previously published work on the ability of similar manoeuvres to increase the carotid sinus nerve (CSN) discharge rate. The two sets of data showed several striking similarities: (i) in both cases, the response to a respiratory acidosis was rapid in onset, maintained and reversible; (ii) in both cases, the speed of response to a metabolic acidosis was significantly slower than in (i) but, again, it was maintained and reversible; (iii) in both cases, increases in PCO2 at constant pHo elicited a rapid response but one which was only transient with no change in the steady-state value. 7. The close correlation between the effects of changing pHo, PCO2 and [HCO3-]o on pHi and on CSN discharge suggests that a change in type-I cell pHi is the first step in the chemoreception of blood pH by the carotid body.(ABSTRACT TRUNCATED AT 400 WORDS)